SEASONAL ABUNDANCE OF LARVAE AND POST-LARVAE OF THE COMMERCIALLY IMPORTANT PENAEID PRAWNS IN THE INSHORE WATERS OF COCHIN - Rao, P Vedavyasa (Indian Journal of Fisheries, 2011)
Seasonal distribution of the larvae and post-larvae of five species of thecommercially important penaeid prawns of the Cochin area during the years 1966-67, 1967-68 and 1968-69 showed that the larvae and post-larvas of Metapenaeusdobsoni form;d a major component (80%) of the total larval population in theinshore waters. The larvae and post-larvae of Parapenaeopsis stylifera were nextin the order of abundance. The annual fluctuations in the occurrence of thelarvae and post-larvae of Metapenaeus monoceros, M. affinis and Penaeus indicuswere very wide. The percentage reduction in the total number, from larvae topost-larvae, which was attributed as mortality rate, varied from year to year indifferent species. Most of these species breed throughout the year with twopeak'si one during October-December which is common to all the species andthj other which is less pronounced extends from May to August. The larvaeof most of the species are able to withstand a wide range in salinity. The larvaeof P. stylifera are generally absent in the inshore waters during the monsoonmonths. A greater abundance of the larvae in the inshore waters during theyear seems to indicate a good prawn fishery in the subsequent season.